Sustainability Performance: Tone in the Disclosure of Non-Financial Information in Sustainability Reports - José CABEDO; José TIRADO; Dennis MUNOZ (Communications of International Proceedings, 2020)
The main objective of this paper is to analyze the state of the art in research on the use of tone in sustainability reports. We set out to select papers that analyze the existence of bias in the tone of disclosures, specifically in the field of environmental information, in favor of the interests of companies’ managers. We carried out a systematic review in the Scopus database and selected 33 articles published between 2000 and 2020. We identified several lines of research that analyze the relationship between tone and the information disclosed in sustainability reports, including one that relates impression management (tone manipulation) to environmental performance. Our work reveals a lack of research on tone in mandatory sustainability reports prepared under the new GRI Standards. By identifying the main lines of research on the topic and the ones with a significant lack of research, this paper contributes to the debate on impression management (tone manipulation) and incremental information in sustainability reports.
Keywords: Tone and disclosure; sustainability reporting; tone management; qualitative disclosure; textual analysis.